Migration and memory: assyrian identity in Merdin Kerboran/Dargeçit - Aras, Ramazan. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
This thesis attempts to analyze the personal narratives and the life stories of Assyrians who lived and Kurdish people living in Kerboran/Dargeçit, Mardin. Focusing on the period between 1910-1980, it examines the migration, memory and identity structures of Assyrian and Kurdish communities in the region. Situating the local history of Kerboran/Dargeçit within the larger historical literature on Assyrian history, the thesis introduces new oral history material. The oral narratives and life stories which form the basis for this thesis are based upon a fieldwork conducted in Kerboran/Dargeçit, in Bakırköy and Yeşilköy regions in Istanbul and in Norrköping and Linköping cities in Sweden in different times since the summer of 2001. This study therefore also follows a multi-sited ethnographic analysis in searching for the historical relationships between Assyrian and Kurdish communities in that particular region.
Keywords: Assyrians -- Turkey.; Assyrians -- History.; Syriac Christians.